Adapting the Middle Section of Verse 4 of Surah Maryam to Order Theory - Hamide Arghavani Beydokhti; Mahmood khorsandi; Seyed Reza Mirahmadi (مطالعات زبانی و بلاغی)
Order in view of Abdul Ghaher includes continuity of words to each other that obtained based on the meanings, provisions, and funds. He believes that: the miracle of Quran based on the order is arising from submission, delay, mention, elimination, definition, contact, separation, and castle. In this article we try to express the continuity of words in creating the image of metaphors such as: “EshtaeloAlraasShiba” of verse 4 of surah Maryam based on order theory and with descriptive-analytical method. The beauty of available metaphor according to Abdul Ghaher Jorjani is due to other factors such as: the word indefinite “Shiba” or the “Al” on the “Alraas”. This metaphor have more than 10 comprehensive that complete the picture have been achieved from particular type of choosing the right nickname.